Recalibrating Legal Reforms: A Critical Examination Of Their Structural Implications On Minority Rights In Contemporary Governance - Shukla, Akshay; Grewal, Upendra (Journal of Neonatal Surgery, 2025)
the calibration of legal reforms and their structural implications on minority rights in contemporary governance. Modern legal reforms, aimed at streamlining policy and enhancing efficiency, often unwittingly undermine the protective frameworks for vulnerable groups. Through a critical lens, this study analyzes how such reforms reshape institutional structures, leaving gaps in safeguards against discrimination and marginalization. Key challenges include the dilution of specific affirmative action provisions, which were designed to counter historical injustices, and the shift towards uniform legal standards that overlook cultural diversity. Empirical evidence from recent governance models demonstrates increased precarity for minority communities, with reduced access to justice mechanisms and policy consultation. Nevertheless, opportunities exist for rebalancing through integrated impact assessments and strengthened equality bodies. This examination advocates for a holistic approach, emphasizing proactive measures to align reforms with international human rights norms. Ultimately, recalibrating must prioritize minority protection to foster sustainable and inclusive governance. Legal Reforms Reforms, Minority Rights, Structural Implications, Contemporary Governance, Critical Examination.